Vegetation Structure of Tree Types on Oil Palm Plasma Plantation Forest Land in Sari Tani Village, Wonosari District, Boalemo Regency - Ahmad, Nur Rahmin; Baderan, Dewi Wahyuni K.; Hamidun, Marini Susanti; Febriyanti, Febriyanti; Husain, Ilyas H. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Some of the dangers of opening oil palm plantations for the environment are that many forests are cut down because they are used as oil palm plantations. The research was conducted in Sari Tani Village, Wonosari District, Boalemo Regency, Gorontalo Province. The research was conducted in December 2024. This study aims to analyze the vegetation structure in the oil palm plasma plantation forest land of Sari Tani Village. The type of research used is quantitative descriptive. This study uses the line transect method consisting of three stations. Plots measuring 20x20 m are used for tree-level vegetation analysis with a distance between plots of 20 m. The data analysis technique uses the Important Value Index (INP) formula. So that 9 types of plants were found in the oil palm plasma plantation forest land of Sari Tani Village. The highest Important Value Index (INP) in station I was Aren (Arenga pinnata) at 75.48%; in station II, Matoa (Pometia pinnata) at 65.86%; and in station III, namely Benying (Ficus fistulosa) at 76.79%.